PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN PEMBUATAN MIND MAP DI KELAS IV SDN - Fitri, Eka Maidia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on the preliminary observation, it was found that student’s achievement on social subjects still low. Therefore, researcher through this study tried to increase students achievement by making Mind Map in learning social subjects of the fourth grade students in SDN 28 Parit Rantang Kecamatan Payakumbuh Barat Kota Payakumbuh. This Mind Map was done seven steps. This study used qualitative and quantitative approad, in form of calssroom action research. This research was done in two cycle. Cycle I was two meetings, and cycle II was one meeting. In cnclusion, learning social subjects by making Mind Map can increase students achievement. Of the fourth grade student in SDN 28 Parit Rantang Kecamatan Payakumbuh Timur Kota Payakumbuh. Kata Kunci : hasil belajar siswa pada pembelajaran ips dengan pembuatan mind map